Strengthening the work ethic of business actors in the Girilayu Batik industry - Wijaya, Mahendra Wijaya; Pujihartati, Sri Hilmi; Sudarsana, Sudarsana; Adi, Yustia Atsanatrilova; Putri, Alfina Ananda; Andira, Dinda Andira (Universitas Islam Sultan Agung, 2025)
The batik industry, as part of Indonesia’s creative economy and cultural heritage, faces challenges in maintaining competitiveness while preserving traditional values. This study aims to examine the work ethic patterns of batik entrepreneurs in Girilayu Village, Matesih District, Karanganyar Regency, and to identify the supporting and inhibiting factors in strengthening them. A qualitative approach was employed through in-depth interviews, observations, and Focus Group Discussions with members of the Batik Giriarum association. The findings show that the work ethic of Girilayu batik makers is marked by flexible time management, independence, and economic motivation based on direct needs. The diffusion of productive values occurs through social agents such as group leaders and senior artisans. Supporting factors include collective culture, personal responsibility, and community support, while the absence of structured time management, incentive systems, and training serves as an inhibiting factor. Using Rogers’ innovation diffusion theory, the study concludes that strengthening the community-based work ethic is crucial for sustaining local creative industries.